Clonally Expanded Decidual Effector Regulatory T Cells Increase in Late Gestation of Normal Pregnancy, but Not in Preeclampsia, in Humans - Tsuda, Sayaka; Zhang, Xiaoxin; Hamana, Hiroshi; Shima, Tomoko; Ushijima, Akemi; Tsuda, Kei; Muraguchi, Atsushi; Kishi, Hiroyuki; Saito, Shigeru (Frontiers in Immunology, 2018)
Background: Regulatory T (Treg) cells are necessary for the maintenance of allogenic pregnancy. However, the repertoire of effector Treg cells at the feto-maternal interface in human pregnancy remains unknown. Our objective was to study T cell receptor (TCR) repertoires of Treg cells during pregnancy compared to normal and complicated pregnancies. Methods: Paired samples of peripheral blood and decidua in induced abortion and miscarriage cases were obtained from consenting patients. CD4+CD25+CD127low/−CD45RA− effector Treg cells were single-cell sorted from mononuclear cells. cDNAs of complementarity determining region 3 (CDR3) in TCRβ were amplified from the single cells by RT-PCR and the sequences were analyzed. The TCRβ repertoires were determined by amino acid and nucleotide sequences. Treg cells were classified into clonally expanded and non-expanded populations by CDR3 sequences. Results: We enrolled nine induced abortion cases in the 1st trimester, 12 cases delivered without complications in the 3rd trimester, 11 miscarriages with abnormal chromosomal karyotyped embryo, seven miscarriages with normal chromosomal karyotyped embryo, and seven cases of preeclampsia (median gestational week (interquartile range): 7 (7-9), 39 (38-40), 9 (8-10), 8 (8-10), and 34 (32-37), respectively). The frequency of clonally expanded populations of effector Treg cells increased in decidua of 3rd trimester cases compared to 1st trimester cases (4.5% (1.4-10.8%) vs 20.9% (15.4-28.1%), p<0.001). Clonally expanded Treg cells were rarely seen in peripheral blood. The ratio of clonally expanded populations of decidual effector Treg cells in miscarriages with abnormal and normal embryos was not significantly different compared with that in 1st trimester normal pregnancy. Interestingly, clonally expanded populations of effector Treg cells decreased in preeclampsia compared with that in 3rd trimester normal pregnancy (9.3% (4.4-14.5%) vs 20.9% (15.4-28.1%), p = 0.003). When repertoires in previous pregnancy and subsequent pregnancy were compared, some portions of the repertoire were shared. Conclusion: TCR repertoires of decidual effector Treg cells are skewed in the 3rd trimester of normal pregnancy. Failure of clonal expansion of populations of decidual effector Treg cells might be related to the development of preeclampsia.